2015
DOI: 10.1371/journal.pone.0124771
|View full text |Cite
|
Sign up to set email alerts
|

Tim-4 Inhibits NO Generation by Murine Macrophages

Abstract: ObjectiveT cell immunoglobulin- and mucin-domain-containing molecule-4 (Tim-4) receives much attention as a potentially negative regulator of immune responses. However, its modulation on macrophages has not been fully elucidated so far. This study aimed to identify the role of Tim-4 in nitric oxide (NO) modulation.MethodsMacrophages were stimulated with 100 ng/ml LPS or 100 U/ml IFN-γ. RT-PCR was performed to detect TIM-4 mRNA expression. Tim-4 blocking antibody and NF-κB inhibitory ligand were involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Although Con A-induced liver injury is a T cellmediated autoimmune hepatitis model (36), it has been found that Kupffer cells are involved in the initiation and propagation of liver damages (37), suggesting that Tim-4 expressed on macrophages might attenuate the priming and activation of T cell responses in Con A-induced hepatitis. Further analysis showed that Tim-4 inhibited cytokines and NO production via the NF-κB or Jak2/STAT1 signaling pathways (14). Taken together, we speculate that Tim-4 may play an inhibitory role in the course of macrophage activation.…”
Section: Macrophagesmentioning
confidence: 68%
See 2 more Smart Citations
“…Although Con A-induced liver injury is a T cellmediated autoimmune hepatitis model (36), it has been found that Kupffer cells are involved in the initiation and propagation of liver damages (37), suggesting that Tim-4 expressed on macrophages might attenuate the priming and activation of T cell responses in Con A-induced hepatitis. Further analysis showed that Tim-4 inhibited cytokines and NO production via the NF-κB or Jak2/STAT1 signaling pathways (14). Taken together, we speculate that Tim-4 may play an inhibitory role in the course of macrophage activation.…”
Section: Macrophagesmentioning
confidence: 68%
“…We reported that Tim-4 inhibited the expression of CD80, CD86, MHC-II and the production of TNF-α in LPS-treated macrophages (15). Tim-4 could also suppress nitric oxide (NO) production in LPS-or IFN-γ-activated macrophages (14). Furthermore, Tim-4 was shown to protect mice from ConA-induced liver injury or LPS-induced septic shock by inhibiting pro-inflammatory cytokines such as IL-6 and TNFα (15,35).…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that LPS, IFN-γ and ConA could enhance TIM-4 expression in macrophages. 23,24 It was also reported that damage-associated molecular patterns released from chemotherapy-damaged tumour cells induced TIM-4 expression on tumour-associated macrophages and dendritic cells. 25 Recent studies have shown that TIM-4 is overexpressed in several tumours, 26,27 which is related with the worse prognosis of lung cancer as PD-L1, which further aggravated the tumour development.…”
Section: Discussionmentioning
confidence: 98%
“…Nuclear factor-κB (NF-κB), a vital activator in inflammatory processes, can regulate the expression of inflammatory cytokines and mediators, and chemokines in many cell types, including macrophages [19][20][21]. Under normal condition of cells, NF-κB exists in an inactive form by combining with its inhibitory protein (IκB) in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%